Approximate Controllability of Second-order Neutral Stochastic Non-autonomous Integrodifferential Inclusions by Resolvent Operators - Nirmalkumar, R.; Murugesu, R. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we formulate a set of sufficient conditions for the approximate controllability for a class of second-order neutral stochastic nonautonomous integrodifferential inclusions in Hilbert space. We establish the results with the help of resolvent operators and Bohnenblust-Karlin’s fixed point theorem is to prove the main result. An application is given to illustrate the main result.